DEVELOPING ICT-BASED CALCULUS LEARNING MEDIA - Tri Hidayati; Ines Heidiani Ikasari (JPMI (Jurnal Pendidikan Matematika Indonesia), 2020)
The purpose of this study is to produce information and communication technology/ICT-based calculus learning media that meets the valid, practical, and effective criteria. This type of research is development research. The development model used is the ADDIE model. According to Pribadi (2009: 125) one of the learning system design models with basic stages of learning system design that is simple and easy to learn is the ADDIE model. ADDIE stands for Analysis, Design, Development, Implementation, and Evaluation. The ADDIE model was developed by Reiser and Mollenda (Branch. 2009: 17-18). Validity data was obtained from validation results by material experts, media experts, and user lecturers. While practicality data is obtained from lecturers' decisions, student responses and the implementation of the learning process (lectures). For effectiveness analysis, it is done by determining the percentage of students who reach the minimum high category for the motivation questionnaire and determining the percentage of completeness of students' scores on classical learning achievement tests. Modules will be categorized as valid and practical if each review minimally is considered to the "good" category, whereas it is effective if students who achieve classical completeness of at least 80% for achievement tests and a minimum questionnaire assessment of the "good" category.